2015
DOI: 10.3390/w7116228
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of Time-Averaged Suspended Sediment Concentration in the Nearshore

Abstract: Abstract:To quantify the effect of wave breaking turbulence on sediment transport in the nearshore, the vertical distribution of time-averaged suspended sediment concentration (SSC) in the surf zone was parameterized in terms of the turbulent kinetic energy (TKE) at different cross-shore locations, including the bar crest, bar trough, and inner surf zone. Using data from a large-scale laboratory experiment, a simple relationship was developed between the time-averaged SSC and the time-averaged TKE. The vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Laboratory (Steetzel, 1993, Roelvink and Reniers, 1995, van Thiel de Vries et al, 2008 and field studies (Nielsen, 1984, Yu et al, 1993, Beach and Sternberg, 1996 have reported large amounts of suspended sediment in the breaking zone, related to the enhancing effects of breaking-generated vortices on sediment entrainment from the bed (Nielsen, 1984, Nadaoka et al, 1988, van Thiel de Vries et al, 2008, Scott et al, 2009, Aagaard and Hughes, 2010, Sumer et al, 2013 and on vertical sediment mixing (Nielsen, 1984, Ogston and Sternberg, 2002, Aagaard and Jensen, 2013, Yoon et al, 2015. These processes depend on the characteristics of the breaking wave, with plunging breakers being more effective in entraining and mixing sediment than spilling breakers (Nielsen, 1984, Aagaard andJensen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory (Steetzel, 1993, Roelvink and Reniers, 1995, van Thiel de Vries et al, 2008 and field studies (Nielsen, 1984, Yu et al, 1993, Beach and Sternberg, 1996 have reported large amounts of suspended sediment in the breaking zone, related to the enhancing effects of breaking-generated vortices on sediment entrainment from the bed (Nielsen, 1984, Nadaoka et al, 1988, van Thiel de Vries et al, 2008, Scott et al, 2009, Aagaard and Hughes, 2010, Sumer et al, 2013 and on vertical sediment mixing (Nielsen, 1984, Ogston and Sternberg, 2002, Aagaard and Jensen, 2013, Yoon et al, 2015. These processes depend on the characteristics of the breaking wave, with plunging breakers being more effective in entraining and mixing sediment than spilling breakers (Nielsen, 1984, Aagaard andJensen, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Field observations [77,90] have shown that sediment clouds lifted by plunging breaker vortices can extend a significant distance above the bed (up to z > 50 cm) and Figure 10 shows that when plunging is violent, the clouds may occupy the entire water column. Laboratory experiments in wave flumes have shown that inside the surf zone, mean sediment concentrations indeed scale with k rather than with u (or u 2 ; [91,92]). Since k scales with γ (Figure 6), it might be expected that there is also a relationship between SSC and γ.…”
Section: Sediment Mobilization and Time-averaged Sediment Concentrationmentioning
confidence: 99%
“…Laboratory experiments in wave flumes have shown that inside the surf zone, mean sediment concentrations indeed scale with k rather than with u (or u 2 ; [91,92]). Since k scales with γ (Figure 6), it might be expected that there is also a relationship between SSC and γ.…”
Section: Sediment Mobilization and Time-averaged Sediment Concentrationmentioning
confidence: 99%
“…This mixed layer (l m ) is comprised between 0.1 and 1 m (Aagaard and Jensen, 2013); we took 0.5 m in average. Assuming that the sediment concentration decreases from the bottom (C o ) to the top of the mixing layer following an exponential law (Figure 4, C o = 1 kg m −3 , Aagaard and Jensen, 2013;Yoon et al, 2015), we took an average sediment concentration of 0.42 kg m −3 in the mixed layer. Based on simple geometrical characteristics shown in Figure 4, the volume of the mixed zone is:…”
Section: Simentioning
confidence: 99%